2015
DOI: 10.12707/riv14013
|View full text |Cite
|
Sign up to set email alerts
|

Pain assessment in children with cancer: a systematic review

Abstract: ResumoResumen R E V I E W P A P E R Background: The peculiarities of persistent pain in children with cancer make its assessment difficult. Aim: The aim was to identify persistent pain assessment tools and indicators related to this experience that have been used in children with cancer. Method of Review: Using Medline and CINAHL databases, primary studies between 2003 and 2013 assessing pain experience in children (0-18 years) with cancer were selected. The selection of studies, assessment of methodological q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
(10 reference statements)
0
6
0
4
Order By: Relevance
“…The application of FPS-R, in general, was receptive to the evaluated children and allowed to analyze intensity or pain score, verify its prevalence; however, it was not the scope of this research to relate it to the monitoring of pharmacological treatment practices or not of pain, as found in a study in Portugal (10) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of FPS-R, in general, was receptive to the evaluated children and allowed to analyze intensity or pain score, verify its prevalence; however, it was not the scope of this research to relate it to the monitoring of pharmacological treatment practices or not of pain, as found in a study in Portugal (10) .…”
Section: Discussionmentioning
confidence: 99%
“…These instruments can be of self-assessment, when the child himself reports through figures and colors the pattern of pain felt at the time, or by an evaluator who, by observing the child's behavior, determines the pain score. In addition to intensity and location, the multidimensional evaluates the quality of pain in the sensory, sensory, evaluative and temporal dimensions (10) .…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it is observed that the literature (6,(9)(10)(11) on the subject on the screen has focused mainly on the evaluation and management of chronic cancer pain in the child, pointing out important professional barriers in performing both processes. In this direction, the present research has originality when addressing the limiting and/or facilitating conditions that permeate the care management for the hospitalized child with chronic cancer pain, under the theoretical perspective of the dialogic principle of complexity, relying on the Grounded Theory method, considering, in this particular, not only the actions of evaluation and management of pain, but also the relational and organizational context of care.…”
Section: Introductionmentioning
confidence: 99%
“…A compreensão subsidiada pela percepção profissional pode ajudar a equipe de enfermagem a traçar estratégias mantenedoras da qualidade assistencial, bem como a lidar com as marcas da complexidade no âmbito do planejamento das ações (7) que permeiam as relações de cuidado, a saber: incertezas, desafios, imprevisibilidades e a condição multidimensional da dor oncológica crônica. É, portanto, uma possibilidade de avançar nos estudos sobre o tema, os quais têm se concentrado na avaliação e no manejo da dor oncológica (8)(9)(10)(11) . Desse modo, questiona-se: Como os profis- (7) .…”
Section: Introductionunclassified